A quantification model using P3P in privacy control for telecommunications service management. (25th July 2005) - Choi, Young B.; Seo, Hyewon; Blackburn, Jonathan M.
The public are becoming increasingly concerned about the privacy invasion via the internet. The information privacy in telecommunications service management, privacy laws, especially the Online Privacy Act of 2003, and use of Platform for Privacy Preference (P3P) are discussed in this paper. Then, a quantification model using P3P in privacy control is suggested.